Phosphorous Immobility During Formation of the Layered Sulfate Deposits of the Burns Formation at Meridiani Planum. Issue 5 (23rd May 2018) - McCollom, Thomas M.; Donaldson, Chris; Moskowitz, Bruce; Berquó, Thelma S.; Hynek, Brian
Abstract: The relatively high abundance of phosphorous (P) in rocks from the Martian crust makes it a potentially useful element for tracking geochemical processes. Owing to the high solubility of common P‐bearing minerals such as apatite at low pH, P is widely thought to be mobile under acid‐sulfate conditions. Accordingly, transport of P by acidic fluids has been invoked to explain enrichments or depletions of this element in some rocks and soils from Mars. The sediments that compose the layered‐sulfate deposits of the Burns formation at Meridiani Planum were originally derived from a basaltic precursor but appear to have been exposed to acidic, sulfate‐rich fluids at several intervals during their history. Yet, assessment of the chemical composition of the bedrocks indicates that they maintain pristine igneous P:Ti ratios and P abundances similar to Martian basalts, indicating that there has been little or no transport of P into or out of the deposits at any stage in their formation. Potential reservoirs for P in the deposits include basaltic glass, secondary Fe‐ or Al‐phosphate minerals, substitution of PO4 for SO4 in alunite‐jarosite group minerals, or surface adsorption. Although Fe‐phosphates were not among the minerals detected by the Mössbauer spectrometer onboard the Opportunity rover at Meridiani, it might be difficult to detect such minerals even if they are present because they are below the detection limit or have signatures similar to other minerals. Overall, the results demonstrate that P can be immobile even in some acid‐sulfate environments on Mars and Earth. Plain Language Summary: The bedrocks at the landing site of the Opportunity rover on Meridiani Panum, Mars, are standstones composed of sulfate mineral and altered basalt components. The sand was deposited at Meridiani by wind and water, and then underwent further mineral and chemical alteration by infiltrating groundwater. At several stages during formation of the bedrocks, the sediments interacted with acidic, sulfate‐rich fluids. The element phosphorous is commonly thought to be mobile under acidic conditions, and transport by acidic fluids is thought to be responsible for addition or removal of phosphorous in some rocks and soils at other locations on Mars. Yet analysis of chemical data obtained by the Opportunity rover at Meridiani indicates that phosphorous was not transported into or out of the rocks to any significant degree, despite the influx of acidic fluids at several intervals during their formation. This result provides a new constraint that can be used to test alternative models for the origin of the bedrocks. Key Points: Rover data indicate that phosphorous was essentially immobile at all stages in the formation of the sulfate‐rich bedrocks at Meridiani Results from a terrestrial analog and lab experiments confirm that P can be immobile under some acid‐sulfate conditions Potential reservoirs for P include basaltic glass, Fe‐ or Al‐phosphates, alunite‐jarosite group minerals, and surface adsorption